Memory Lingualized in the of People in the Period of Middle Adulthood - Gocół, Damian (Vilnius University Open Series, 2020)
In my article, I analyze the way people in their middle adulthood (35–65 years old) talk about their own biographical experience. By comparing the relations selected from my own collection, I try to indicate what the ways of linguistic expression are used to build a biographical narrative and a conversation with the researcher. The aim of the article is to show how non-linguistic factors (profession, social status, education, experience or gender) influence the structure of the story, the choice of the narrative schemes and the ways of linguistic expression. In the analyzed texts clearly shows the structuring of the narrative by means of images, scenes and narrative sequences. They allow for the reconstruction of the narrative schemes in the mostly statements related to the talking about maturation.
Keywords: memory; oral history; narrative; narrative scheme; middle adulthood